1968
DOI: 10.1042/bj1100035pa
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of barley limit dextrinase

Abstract: 35P ofits conversion into fibrous hydroglucan (Houwink & Kreger, 1953). We thank Dr C. T. Bishop for a sample of glucan from Candida parap8ilo8i8 and Mrs E. F. Cruickshank for technical assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
2
7
1
Order By: Relevance
“…These separated activities were given the respective names R-enzyme and limit dextrinase. Manners and coworkers [3,4] have subsequently confirmed the MacWilliam and Harris finding, with the same and with different plant extracts.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…These separated activities were given the respective names R-enzyme and limit dextrinase. Manners and coworkers [3,4] have subsequently confirmed the MacWilliam and Harris finding, with the same and with different plant extracts.…”
Section: Introductionsupporting
confidence: 61%
“…Our inability to correlate our own results with those of MacWilliam and Harris [2] and Manners and coworkers [3,4] has perhaps been overcome following a recent report by Manners, Marshall and Yellowlees [S] , where it is stated that amylopectin P-limit dextrin is a substrate for "limit dextrinase". This is contrary to the report by MacWilliam and Harris [2] but now permits an explanation of what limit dextrinase might be, since under its new definition, it has all the activities originally ascribed to Renzyme [ 11, save that of attacking amylopectin.…”
Section: Introductioncontrasting
confidence: 43%
See 1 more Smart Citation
“…A branching enzyme extract from sweet corn (Zea mays) also acted on amylose and amylopectin but, because of the different pH and temperature optima of the reactions with amylose and amylopectin and the activation by citrate of only the amylose reaction, it was concluded that the extract contained a second branching activity [32]. This was further supported by differences in the heat stabilities and inhibitions by HgC1, of the activities with the two substrates and was subsequently confirmed by the separation of two activities by Manners et al [33]. The first activity branched amylose only and was designated as Q-enzyme, whilst the second activity was similar to the branching enzyme of yeast [34] in that it readily acted on amylose and amylopectin.…”
Section: Purification and Properties Of Potato And-enzymesupporting
confidence: 48%
“…Denaturation of the polysaccharide may be the permissive cause of Q-enzyme action. Claims have been made of the conversion of amylopectin into glycogen by plant branching enzyme preparations [38,39]. Such conversion requires an approximate doubling of the content of branch linkage and halving of the average chain length.…”
Section: -Phosphate; ( -)mentioning
confidence: 99%